NILAI-NILAI FILOSOFIS EMOSI SEBAGAI DASAR BIMBINGAN MENTAL ANAK DI SMK PONDOK PESANTREN AL FALLAH LAMPUNG TENGAH - Wahyudin Wahyudin; Dedi Wahyudi (INSTITUT AGAMA ISLAM NEGERI METRO, 2023)
The role of school institutions in the mental formation of children has long been played by formal institutions. Essentially, every school has forms of local wisdom that are inherent and serve as a resilience system in dealing with a variety of problems. What drove this study was the existence of problems that occur in the SMK Ponpes Al Falah: first, the emotional temperament of children that sometimes leads to fatalism. Second, the child conflict that always reappears occurs between fellow friends and between good classmates sons and daughters who always justify the right. Third, the internal conflict in the classroom that sometimes does not end is caused by the individual's emotions being less able to control themselves.Philosophical values become the form of local norms used by the head of school and teachers in school institutions. Using interpretative analysis of data from observations and interviews, the study found that the philosophical values adhered to by the school's institution formed the foundation for addressing a variety of problems. The study found that the philosophical values adhered to by the school institutions form the foundation for addressing a variety of problems. The principal, who also serves as a dynamic force in this study, has important roles to play in terms of socialisation, integration, normative influence, and social control. The use of philosophical values in this article successfully demonstrates that philosophical values as a form of mechanism in mental formation can address social problems in the school environment.